Localization of Drosophila CENP-A to non-centromeric sites depends on the NuRD complex - Demirdizen, Engin; Spiller-Becker, Matthias; Förtsch, Arion; Wilhelm, Alexander; Corless, Samuel; Bade, Debora; Bergner, Andrea; Heßling, Bernd; Erhardt, Sylvia (Nucleic acids research, 2019)
Abstract. Centromere function requires the presence of the histone H3 variant CENP-A in most eukaryotes. The precise localization and protein amount of CENP-A
Gesehen am 17.04.2020